PARTISIPASI MASYARAKAT DALAM PENGELOLAAN POTENSI PARIWISATA SUBAK SUKAWAYAH UBUD - Baskara, I Made Cahya; Zuryani, Nazrina; Arjawa, I G.P.B Suka (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT This study aims to get clear overview on tourism potency that exist at Subak Sukawayah Ubud, and to study participation of subak member (krama subak) in management of tourism potencyÂ at Subak Sukawayah Ubud, and to find out furthermore on obstacle of subak member participation in manage of potency owned by Subak Sukawayah. This study used qualitative method. Data was collected by observation, interview, and documentation. Data analysis technique is qualitative descriptive analysis. The result shows that: (1) there are three components of tourism potency at Subak Sukawayah that are, physic/nature, biotic, and culture social, that can be developed in many manifestation of attraction and tourism activity. (2) management of tourism potency of Subak Sukawayah not yet entangle of subak member participation in process of planning, implementation, benefit taken and evaluation (3) internal factor that blocking of subak member in participation to manage of potency of Subak Sukawayah as tourism attraction that are, ability of subak member human resource, institution of subak manager that still weak in response of tourism development, and weakness of manager in eforcement of awig-awig (subak law). While from external factor that are not yet exist harmonisation of management of tourism potency at Subak Sukawayah between entangle party, tourism provider (accomodation) domination by investor, and not yet exist the regulation which arrangement and environment conservation of subak physic. Keywords: tourism potency, tourism management, public participation, Subak Sukawayah.